PENERAPAN MODEL SAVI DALAM PEMBELAJARAN TARI SIGEH PENGUNTEN DI MAN 1 BANDAR LAMPUNG - Zairi Zairi (Jurnal Seni dan Pembelajaran, 2015)
ABSTRACTAPPLYING SAVI MODEL IN SIGEH PENGUNTEN DANCE LEARNING OF MAN 1 BANDAR LAMPUNGByZairiThis aims to describe the application of the model SAVI and student learning outcomes in teaching dance class X sigeh pengunten IAI MAN I Model Bandar Lampung. The model used in this research is qualitative descriptive. Source of data in this study is a teacher of dance and 38.the data teching collection are observation, interviews, documentation, test practice, and application of models SAVI nontes. Implementation of the first formulated goals to be achieved. second prepare means of learning. Third notify SAVI learning that will be used. Fourth inform instructional material namely Sigeh Pengunten dance. Fifth giving students the opportunity to ask. Sixth gives the task. Seventh evaluate learning the results assesment providedthrough four aspects, they are, namely, somatic, auditory, visual, intellectual and assessment of student learning activities. learning outcomes showed an average velue of 71.58 means learning sigeh pengunten dence using SAVI models can be well applied with the application of the measures.Keywords: SAVI models, sigeh pengunten dance, and assessment